Redefining the Success of Education: Where Indonesia Has Excelled and Where It Has Not - Henry Wijaya (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
How do we define the state of Indonesia’s national education? On one hand, Indonesian students have always performed lamentably in international standardized tests. In the latest 2015 PISA test, their performance in Science, Mathematics, and Reading was among the lowest, with the average ranking of 62 out of the 70 participating countries (OECD, 2016). On the other hand, Indonesia’s enrollment rates for primary education have always been higher than 97% for the past decade (Statistics Indonesia, 2018), with the Gross Enrollment Ratio even reaching 103.45% in 2016 (World Bank, 2016). With such polarizing results, it is not easy to give a clear-cut answer to above question. However, in retrospect, should the success of Indonesia’s education be measured merely by numbers, in isolation from how it could socioculturally and politically impacted its citizens? Multiple societal tensions, as well as the looming 2019 election, should actually inform us how education should and could play a larger role in countering currently growing conservatism. This paper will first lay out multiple facets of Indonesia’s national education—examining whether one area has fared better than the others—before making a case for the other role that Indonesia’s education policy has not yet pondered, let alone incorporated. Ultimately, this paper expects to contribute to the wider discussion of the overarching question: how the success of national education should be (re-)defined.